FABRIC QUALITY AND PROPERTIES CONSIDER FOR SPORTS WEAR- AESTHETIC AND FUNCTIONAL NEED. - Agarwal, Smriti; Mehta, Sandeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explored experts' perspectives on sports clothing quality, key attributes, and evaluation processes. Twenty-two experts in sports clothing development and evaluation were interviewed using semi-structured methods. Thematic analysis revealed three perspectives on quality, challenges in the evaluation process, and a framework for assessing sports clothing quality. Experts viewed quality as fulfilling use-case requirements, creating an immediate impression, or reflecting individual perception. The framework deconstructed overall quality into attributes and linked them to specific evaluation methods. Challenges such as limited measurability of attributes were identified, with digitalization proposed as a potential solution.